2012
DOI: 10.1371/journal.pone.0041041
|View full text |Cite
|
Sign up to set email alerts
|

Role of Heat-Stable Enterotoxins in the Induction of Early Immune Responses in Piglets after Infection with Enterotoxigenic Escherichia coli

Abstract: Enterotoxigenic Escherichia coli (ETEC) strains that produce heat-stable (ST) and/or heat - labile (LT) enterotoxins are cause of post – weaning diarrhea in piglets. However, the relative importance of the different enterotoxins in host immune responses against ETEC infection has been poorly defined. In the present study, several isogenic mutant strains of an O149:F4ac + , LT + STa + STb + ETEC st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 77 publications
8
61
0
Order By: Relevance
“…ϩ ETEC challenge (0 h) and at 6,12,24,48,96, and 144 h after challenge. Blood samples were collected into Venoject glass tubes (Terumo Europe NV, Leuven, Belgium) containing EDTA, and analyzed fresh for total and differential blood leukocyte counts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ϩ ETEC challenge (0 h) and at 6,12,24,48,96, and 144 h after challenge. Blood samples were collected into Venoject glass tubes (Terumo Europe NV, Leuven, Belgium) containing EDTA, and analyzed fresh for total and differential blood leukocyte counts.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it has been reported that probiotic Lactobacillus casei inhibited the antigen-induced secretion of IL-17 by CD4 ϩ T cells developed from murine Peyer's patch cells (11). A recent study has shown that IL-17 mRNA expression was upregulated in the intestine of pigs after infection with ETEC (12). However, in pigs neither the host sensing systems responsible for inducing early IL-17 secretion nor the nature of the Th17 response to pathogenic and probiotic bacteria in vivo has been elucidated.…”
mentioning
confidence: 99%
“…On the other hand, Loos et al [235] suggested a major role for STb in the early secretory response in 5-week-old piglets. The discrepancy observed could be explained by a difference in age of the piglets used, confirming that this parameter is a crucial element to take into account when evaluating toxicity.…”
Section: Relative Importance Of Etec Toxins In Pathogenesismentioning
confidence: 98%
“…The contribution of different enterotoxins produced by an F4 + ETEC strain (O149, F4ac + , LT + , STa + , and STb + ) to the induction of small intestinal secretion and early innate immune responses were investigated in weaned piglets using isogenic deletion mutants [235]. Net fluid absorption of pig small intestinal mucosa was measured 4 h after infection, allowing for correlation of enterotoxin secretion with gene regulation using microarray analysis.…”
Section: Relative Importance Of Etec Toxins In Pathogenesismentioning
confidence: 99%
“…The inoculum containing the K88-positive ETEC strain, isolated from pigs with colibacillosis, also expressed heat-labile (LT) and heat-stable B (STb) toxins (Loos et al, 2012), and was prepared accordingly to the methods of Bosi et al (2004). A one-way traffic path was implemented to prevent non-challenged pigs to contact with challenged pigs.…”
Section: Animals and Treatmentsmentioning
confidence: 99%